Characterization of PVdF-HFP-based nanocomposite plasticized polymer electrolytes. Issue 4 (15th June 2017) - Sharma, Shuchi; Pathak, Dinesh; Dhiman, Naresh; Kumar, Rajiv
Abstract : Nanocomposite polymer electrolytes based on poly(vinylidene fluoride- co -hexafluoropropylene) (PVdF-HFP) have been prepared by using ammonium fluoride (NH4 F) as salt, dimethylformamide as plasticizer and nanosize alumina (Al2 O3 ) as filler. The ionic conductivity of polymer electrolytes has increased by four orders of magnitude (from 10 −7 to 10 −3 S/cm) with the addition of plasticizer. The conductivity of nanocomposite plasticized polymer electrolytes has increased by a factor of 3–4 with the addition of the nanofiller (alumina) along with an improvement in mechanical strength. The conductivity shows two maxima with the addition of alumina. X-ray diffraction studies have been carried out to check the crystallinity/amorphicity of polymer electrolytes. The small change in conductivity over the 30–130°C temperature range and conductivity remains nearly constant with time suggests that these electrolytes are desirable for their use in electrochemical devices such as batteries, fuel cells, sensors, supercapacitors and electrochromic devices. The activation energies of these electrolytes have also been calculated and correlated with conductivity results.